A picture is worth a thousand words: maps of HIV indicators to inform research, programs, and policy from NA‐ACCORD and CCASAnet clinical cohorts. Issue 1 (4th April 2016) - Althoff, Keri N; Rebeiro, Peter F; Hanna, David B; Padgett, Denis; Horberg, Michael A; Grinsztejn, Beatriz; Abraham, Alison G; Hogg, Robert; Gill, M John; Wolff, Marcelo J; Mayor, Angel; Rachlis, Anita; et al.
Abstract : Introduction: Maps are powerful tools for visualization of differences in health indicators by geographical region, but multi‐country maps of HIV indicators do not exist, perhaps due to lack of consistent data across countries. Our objective was to create maps of four HIV indicators in North, Central, and South American countries. Methods: Using data from the North American AIDS Cohort Collaboration on Research and Design (NA‐ACCORD) and the Caribbean, Central, and South America network for HIV epidemiology (CCASAnet), we mapped median CD4 at presentation for HIV clinical care, proportion retained in HIV primary care, proportion prescribed antiretroviral therapy (ART), and the proportion with suppressed plasma HIV viral load (VL) from 2010 to 2012 for North, Central, and South America. The 15 Canadian and US clinical cohorts and 7 clinical cohorts in Argentina, Brazil, Chile, Haiti, Honduras, Mexico, and Peru represented approximately 2–7% of persons known to be living with HIV in these countries. Results: Study populations were selected for each indicator: median CD4 at presentation for care was estimated among 14, 811 adults; retention was estimated among 87, 979 adults; ART use was estimated among 84, 757 adults; and suppressed VL was estimated among 51, 118 adults. Only three US states and the District of Columbia had a median CD4 at presentation >350 cells/mm 3 . Haiti, Mexico, and several states had >85% retention in care; lower (50–74%) retention in care was observed in the US West, South, and Mid‐Atlantic, and in Argentina, Brazil, and Peru. ART use was highest (90%) in Mexico. The percentages of patients with suppressed VL in the US South and Northeast were lower than in most of Central and South America. Conclusions: These maps provide visualization of gaps in the quality of HIV care and allow for comparison between and within countries as well as monitoring policy and programme goals within geographical boundaries.